Character Formation through Traditional Acehnese Rhymes: A Stylistic Analysis of Moral Meaning - Jesika Lolo Karina Manik; Rosmawaty Harahap (Journal of Aceh Studies, 2026)
Traditional literary forms have long served as culturally embedded means of transmitting ethical values and shaping collective character. In Acehnese society, traditional rhymes constitute an important yet underexamined literary practice through which moral orientations are communicated indirectly via aesthetic and linguistic form. While previous studies have highlighted the educational or thematic value of such rhymes, limited attention has been paid to the role of stylistic features in mediating character formation within specific cultural contexts. This study aims to examine how traditional Acehnese rhymes encode and transmit moral values through their stylistic organization, and to identify the implications of these mechanisms for understanding character formation in Aceh. The study adopts a qualitative research design grounded in stylistic analysis. Data consists of selected traditional Acehnese rhymes sourced from culturally authoritative compilations. The analysis focuses on diction, figurative language, imagery, rhyme patterns, and meaning construction, using an interpretive framework informed by contemporary stylistics and applied linguistics. The findings reveal that moral values such as humility, respect for elders, moral consistency, and social responsibility are embedded systematically in linguistic and aesthetic structures rather than conveyed through explicit moral instruction. Figurative language and imagery drawn from every day and ecological experience function as key mediators of ethical understanding, while regular rhyme patterns enhance memorability and communal circulation. These stylistic elements together form an integrated moral ecosystem that supports character formation within Acehnese cultural life. The study contributes to Aceh Studies by demonstrating how traditional literature operates as a living moral resource. It also offers interdisciplinary insights relevant to character education, cultural sustainability, and the role of local knowledge in contemporary society.